A Study of Stress Management of Private Sector Employees with Special Emphasis on Private Bank Employees (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Stress is an inevitable part of modern professional life, particularly in private sector organizations where performance pressures are high. This paper examines stress levels among private bank employees, identifies key stressors, and evaluates the effectiveness of stress management strategies. The study focuses on analyzing differences in stress levels between top-level and middle-level employees and explores the impact of stress on productivity and health. Findings indicate a significant correlation between effective stress management and improved employee well-being and organizational performance.